Aplicación de las NIIF al inventario y activos fijos de la casa comercial “Adrián” del cantón La Maná, provincia de Cotopaxi, año 2012 - Marcillo Álvarez, María Fernanda (2014)
This research has as aim to explain the reader the application of the International Financial Reporting Standards (IFRS) to the inventory and fixed assets of the commercial office “ADRIAN”, for which the required IFRS are analyzed, the entire company operation is described and subsequently the studied standards are applied, to know the effects on the information of the financial states. The International Financial Reporting Standards are a group of regulations and interpretations that are very important, because these establish the rules for recognition, evaluation.